O funcionamento da máquina de teatro e da máquina do mundo : a metalinguagem teatral de Alcione Araújo - Hickmann, Vanessa (2009)
The following thesis aims to analise the plays of A caravana da ilusão e Doce deleite written by the dramaturge Alcione Araujo, in order to identify all metalanguage sources that can reveal the function of the teather machine as well as the world machine. Furthermore, it´s goal is to purpose a comparative study between the plays, checking the presence of characteristics such as the Aristotelian drama and the epic teather. In the end of the study, the comparison between both, shows that they illustrates the world trough of application of structural sources in dramatic genre that represent the function of theatrical art. The thesis has been based overall on Aristotle, and Bertolt Brecht theories. The important aspects based on the Aristotelian theory are: the delusory atmosphere Catharsis, unit of action, verisimilitude, peripeteia, acknowledgment (recognition). The illusion rupture, the political and social aspects, the single scenes, the detachment are some of the elements analized based on the Brechtian thesis